Apprentice in a changing trade - Perret, Jean-Francois [Verfasser]; Perret-Clermont, Anne-Nelly [Verfasser] (IAP Information Age Publ., 2011)
The main question of this book is what the most appropriate settings for learning in a rapidly evolving industrial context are: In how far are the traditional settings (colleges, businesses and factories) still the best places for the acquisition of professional skills and knowledge? It tackles this question by drawing on a case study of a small vocational training school, the Ecole Technique de Sainte-Croix, situated in the Swiss Jura Montains where young people are about to master the skills of watchmaking. The study was begun in 1993, during a period in the history of this technical college, where first an automated manufacturing system and some time later a robotic assembly unit was installed. (BIBB-Doku)
Keywords: S 1.3.3 Vollzeitschulische Berufsausbildung; S 3.1.2.3 Fachschule (Technikerschule); S 6.2 Fertigungsberufe; G 2.2.1 Technologisierung; L 2.3 Methoden; I 2.2.1 Westeuropa; Schulische Berufsausbildung; Fachschule; Fertigungsberuf; Industrieberuf; Technischer Wandel; Lernort; Lernmethode; Fallstudie; Schweiz